Ampacet develops process aid masterbatch for outdoor blown film applications. Issue 12 (December 2018) - Unknown
Abstract : International masterbatch and additive manufacturer Ampacet has launched process aid masterbatch Proflow 400 (1000400-E), which is designed to ease the processing of blown films that are intended for outdoor use and therefore incorporate UV light stabilizers. According to the company, its new masterbatch outperforms the best-known competitive process aids and market references in blown films.